Cross-sectional and longitudinal relationships between urinary 1-bromopropane metabolite and pulmonary function and underlying role of oxidative damage among urban adults in the Wuhan-Zhuhai cohort in China. (15th November 2022) - Wang, Bin; Fan, Lieyang; Yang, Shijie; Zhou, Min; Mu, Ge; Liu, Wei; Yu, Linling; Yang, Meng; Cheng, Man; Wang, Xing; Qiu, Weihong; Shi, Tingming; et al.
Abstract: 1-bromopropane is a US Environmental Protection Agency-identified significant hazardous air pollutant with concerned adverse respiratory effect. We aimed to investigate the relationship between 1-bromopropane exposure and pulmonary function and the underlying role of oxidative damage, which all remain unknown. Pulmonary function and urinary biomarkers of 1-bromopropane exposure (N-Acetyl-S-(n-propyl)-L-cysteine, BPMA) and oxidative damage to DNA (8-hydroxy-deoxyguanosine, 8-OHdG) and lipid (8-iso-prostaglandin-F2α, 8-iso-PGF2α) were measured for 3259 Chinese urban adults from the Wuhan-Zhuhai cohort. The cross-sectional relationship of BPMA with pulmonary function and the joint relationship of BPMA and 8-OHdG or 8-iso-PGF2α with pulmonary function were investigated by linear mixed models. The mediating roles of 8-OHdG and 8-iso-PGF2α were evaluated by mediation analysis. Additionally, a panel of 138 subjects was randomly convened from the same cohort to evaluate the stability of BPMA repeatedly measured in urine samples collected over consecutive three days and intervals of one, two, and three years, and to estimate the longitudinal relationship of BPMA with pulmonary function change in three years. We found each 3-fold increase in BPMA was cross-sectionally related to FVC and FEV1 reductions by 29.88-mL and 25.67-mL, respectively (all P  < 0.05). Joint relationship of BPMA and 8-OHdG rather than 8-iso-PGF2α with reduced pulmonary function was observed. Moreover, 8-OHdG significantly mediated 9.44% of the BPMA-related FVC reduction. Findings from the panel revealed a fair to excellent stability (intraclass correlation coefficient: 0.43–0.79) of BPMA in repeated urines collected over a period of three years. Besides, BPMA was longitudinally related to pulmonary function reduction in three years: compared with subjects with persistently low BPMA level, those with persistently high BPMA level had 79.08-mL/year and 49.80-mL/year declines in FVC and FEV1, respectively (all P  < 0.05). Conclusively, 1-bromopropane exposure might impair pulmonary function of urban adult population, and oxidative DNA damage might be a potential mechanism underlying 1-bromopropane impairing pulmonary function especially FVC. Graphical abstract: Image 1 Highlights: BPMA was cross-sectionally associated with decreased pulmonary function. BPMA was longitudinally associated with pulmonary function decline in 3 years. 8-OHdG partly mediated BPMA-associated pulmonary function reduction.